2014
DOI: 10.1007/s40618-014-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying subtle changes in cardiovascular mechanics in acromegaly: a Doppler myocardial imaging study

Abstract: ACM pts present LV concentric hypertrophy and LV systolic and diastolic dysfunction, even in controlled disease. Altered global LV systolic function appears to be due both to longitudinal and radial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
6
1
1
Order By: Relevance
“…The decline in left ventricular diastolic function is thought to develop during the early stages of acromegaly. Moreover, systolic dysfunction appears before the progressive impairment of systolic performance, with the latter leading to heart failure [ 9 , 21 , 22 ]. Our results demonstrated that diastolic function was lower in acromegaly patients and that the decline in diastolic function in acromegaly (20.4%, 22/108) was positively related to increased age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in left ventricular diastolic function is thought to develop during the early stages of acromegaly. Moreover, systolic dysfunction appears before the progressive impairment of systolic performance, with the latter leading to heart failure [ 9 , 21 , 22 ]. Our results demonstrated that diastolic function was lower in acromegaly patients and that the decline in diastolic function in acromegaly (20.4%, 22/108) was positively related to increased age and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly is a chronic disease associated with a large number of comorbidities, typically presenting in the first years after diagnosis and not always reversed after disease control, responsible for a significant increase in morbidity, impairment of the quality of life and high mortality rate [1,[3][4][5]. At the same time, due to the disease complexity and variable physi-cian approach to patients, it is currently difficult to obtain a systematic evaluation at diagnosis to be replicated at follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…It mainly occurs sporadically, but may be seen in familial diseases [2]. It is characterized by dysmorphic facial and body features, anatomic and func-tional alterations of internal organs, metabolic, neoplastic and cardiovascular diseases (CVD), neurological symp-toms and hypopituitarism secondary to adenoma mass effect, overall responsible for high morbidity and mortality [1,3,4]. Because of the disease complexity and the vari-able physician approach to patients, it is difficult to obtain a systematic assessment of the numerous complications induced by GH hypersecretion-whose risk and severity are related to disease duration and not always reversed by biochemical control-and its treatments [3,5] and to rep-licate it at the various follow-ups.…”
Section: Introductionmentioning
confidence: 99%
“…Jurcut i wsp. [2] udokumentowali u pacjentów z akromegalią zmniejszenie GLS ocenianego metodą doplera tkankowego. Brakuje natomiast danych dotyczących analizy odkształcenia miokardium techniką śledzenia markerów akustycznych w tej populacji chorych; takiej analizy dokonano u prezentowanego pacjenta.…”
unclassified